2005
DOI: 10.1089/jpm.2005.8.432
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Develop Effective Health Care Decision Making for Women in Prison

Abstract: Those who face chronic, potentially life-limiting illness cannot make meaningful decisions regarding medical care and treatment without having a basic foundation of health information. Acquiring knowledge and improving communication skills reduce stress and vulnerability, assuring individuals of some control over decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…Since 1986 the incarcerated female population has increased by 400%. There are approximately 90,000-100,000 women in United States federal and state prisons (Enders, Paterniti, & Meyers, 2005;Ruiz, 2002). Researchers have found that paternal incarceration usually results in mild to moderate family tensions while on average maternal incarceration may have a greater impact, specifically regarding child placement options and their ability to adjust to new family structures.…”
Section: Shift In Family Structure and Child Placement Issuesmentioning
confidence: 99%
“…Since 1986 the incarcerated female population has increased by 400%. There are approximately 90,000-100,000 women in United States federal and state prisons (Enders, Paterniti, & Meyers, 2005;Ruiz, 2002). Researchers have found that paternal incarceration usually results in mild to moderate family tensions while on average maternal incarceration may have a greater impact, specifically regarding child placement options and their ability to adjust to new family structures.…”
Section: Shift In Family Structure and Child Placement Issuesmentioning
confidence: 99%
“…As a result of limited education and poverty-stricken lifestyles, incarcerated women have typically not had routine access to health care prior to imprisonment (Aday & Krabill, 2011). For instance, women are often lacking in access to reproductive health services and enter prison with unusually high rates of sexually transmitted infections, substance abuse, and histories of poor nutrition (Enders, Paterniti, & Meyers, 2005). Elevated chronic health conditions include asthma, obesity, diabetes, hypertension, anemia, seizures, ulcers, heart disease, obesity, and cancers (Hannaher, 2007;Jacobi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of 'get tough' sentencing policies has resulted in the proliferation of the long-term prisoner population, and the unintended consequence is that a large number of inmates are growing old in prison. Some scholars speculate that older inmates will make up about one-third of the prison population by 2020 (Enders, Paterniti, and Meyers 2005). It is generally estimated that the cost of incarcerating an elderly innate is 3 -5 times more expensive than a younger inmate Hurley 2014;Blowers, Jolley, and Kerbs 2014).…”
Section: Corrections and The Older Offendermentioning
confidence: 99%